Efektivitas Penggunaan Quick Response Code Indonesian Standard (QRIS) pada UMKM (Food and Beverage) di Kabupaten Ponorogo - Septiana Alisa Salsabila; Aji Damanuri (Niqosiya: Journal of Economics and Business Research, 2023)
Advances in technology and digitization have resulted in very rapid developments in community activities such as the payment system. This research is a field research (field research) with a qualitative approach to the type of descriptive research. Where data collection uses interview techniques, observation, and documentation. Data analysis techniques include data reduction, data presentation, and conclusion. The authors use the triangulation technique to check the data's validity. This study concludes that the indicators for achieving goals are said to be effective but not optimal because MSME actors feel the ease of using QRIS, but the main goal is to follow trends; the integration indicators are said to be effective but not optimal because there are still few people who pay using QRIS even though they have received socialization and adaptation indicators are said to be ineffective. After all, the organizers have yet to conduct a follow-up survey on MSME (Food and Beverage) actors who use QRIS.